ANALISIS KESESUAIAN PERAIRAN TAMBAK DI KABUPATEN DEMAK DITINJAU DARI NILAI KLOROFIL-A, SUHU PERMUKAAN PERAIRAN, DAN MUATAN PADATAN TERSUSPENSI MENGGUNAKAN DATA CITRA SATELIT LANDSAT ETM 7+ - Muchlisin Arief; Lestari Laksmi W. (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2006)
Demak district has 4 sub district that are potentially to develop fishpond such as : Sayung, Karang Tengah, Bonang and Wedung sub district. However, recently the fishpond production is decreasing compared to the production in a few years ago. This decreasing is ceused by water quality degradation and the lage of information on the condition of the fishpond. The aims of the research are : to analyse some parameter for the fishpond suitability such as (cholorophyle-a, water surface temparature and suspended solid load_, 2). to analyse some factors on the fishpond suitability based on water primary productivity such as pH, suspended Oxygen, salinity, Nitrate and phosphate. The result of the research shows that : by using the formulation of klor-a (ug/1)=17.912(b1-b2)/(b1+b2)-0.3343 the range value f chlorophyle-a is 0.368-2,852 ug/1, by using the formulation of Tp(℃)= 0.6674(b6)-75.544 obtained the value of water surface temperature is 25.03-40.00(℃), and by using the formulation MPT(ppm)=-15.8049+0.6674(b1)-1.066(b2)+0.9437(b3)+0.1939(b4), the range value of suspended solid load is 26.07-74.00 ppm. Overlaying the above result (maps of chlorophyll-a, water surface temperature, and MPT) added with the information of water primary productivity obtained that the "suitable" fishpond area in Demak, area in Sayung, and Karang Tengah sub district, while "conditionally suitable" area in Bonang and Wedung sub district. This mean that fishpond area in Demak is possible to be developed with the certain treatment.